The effectiveness of the long-lasting insecticidal nets in controlling malaria vector: a meta-analysis of experimental hut studies - Muhammad Faiz Mohd Ishak; Mohd Shahrol Abd Wahil; Haniff Mohd Nawi; Azmawati Mohammed Nawi; Norfazilah Ahmad; Fatimah Ahmedy; Mohammad Saffree Jeffree; Syed Sharizman Syed Abdul Rahim; Mohd Rohaizat Hassan (Universiti Kebangsaan Malaysia, 2025)
Background: Malaria is a life-threatening, preventable, and curable vector borne disease caused by parasites that are transmitted to people through the bites of infected female Anopheles. The WHO Global Report 2010-2016 reported insecticide resistance in malaria. The main objective of this study is to determine the effectiveness of new generation Long-Lasting Insecticidal Nets (LLIN) compared to standard LLIN and untreated nets in terms of the mortality rate of adult female Anopheles gambiae.Methods: A comprehensive review of the literature was published in three databases (PubMed, Ovid, EBSCO Host) since 2010. Publications were searched with keywords including malaria, long-lasting treated bed net, long lasting insecticide-treated bed net, LLIN, and experimental hut. The search has identified 60 articles. Based on the PRISMA flowchart, 10 articles are qualified for data collection and analysis. The gathered data was analysed using Review Manager.Results: Following meta-analysis between subgroups, a risk difference of 0.31 between standard LLINs versus untreated net (p<0.001, I²=100% 95% CI:0.01,0.60). A comparison of upgraded LLINs with the untreated net has shown a significant difference with a pooled risk difference of 0.54 favours upgraded LLINs (p<0.001, I²=100% 95% CI: 0.54,0.84). Comparison between upgraded LLINs versus standard gave an overall risk difference of 0.24 (p < 0.001, I² = 100%, 95% CI: 0.10–0.39).Conclusion: Upgraded LLINs significantly increase Anopheles mortality compared to standard LLINs and untreated nets, suggesting their potential for improved malaria control. Thus, using upgraded nets in the field and translating them into malaria preventive programs would help achieve the target and improve health outcomes for those living in endemic areas.